2022
DOI: 10.1553/populationyearbook2022.res1.5
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and relationship quality: Emotional, paid work and organizational spheres

Abstract: This study contributes to the growing literature on the repercussions of the COVID- 19 pandemic for family functioning, with a special focus on couples’ relationship quality. We advance an analytical model that emphasizes the role of three main stressors of relationship quality during the pandemic: namely, emotional, paid work-related and organizational stressors. To outline such an approach, we analyze whether the onset of the pandemic – and the home confinement that followed – has reduced relationship qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…The pandemic also affected reproductive behavior in more subtle ways. Marriages were postponed, younger people and couples not living together had fewer opportunities to meet, some couples reported worsening relationship quality (Bellani and Vignoli 2022;Schmid et al 2021;Vigl et al 2022) and less frequent sexual intercourse (Lehmiller et al 2020;Luetke et al 2020), families struggled to accommodate home schooling and other needs of their children staying at home, and contact with grandparents-important providers of childcarewas often severely restricted or entirely cut off for many months (e.g., Settersten et al 2020;Berrington et al 2021;Mayer 2022). In short, the coronavirus pandemic was often perceived as a disruptive shock, which brought about new uncertainties (Guetto, Bazzani, and Vignoli 2022) and which would accelerate the long-standing trend to low or very low fertility rates.…”
Section: Introductionmentioning
confidence: 99%
“…The pandemic also affected reproductive behavior in more subtle ways. Marriages were postponed, younger people and couples not living together had fewer opportunities to meet, some couples reported worsening relationship quality (Bellani and Vignoli 2022;Schmid et al 2021;Vigl et al 2022) and less frequent sexual intercourse (Lehmiller et al 2020;Luetke et al 2020), families struggled to accommodate home schooling and other needs of their children staying at home, and contact with grandparents-important providers of childcarewas often severely restricted or entirely cut off for many months (e.g., Settersten et al 2020;Berrington et al 2021;Mayer 2022). In short, the coronavirus pandemic was often perceived as a disruptive shock, which brought about new uncertainties (Guetto, Bazzani, and Vignoli 2022) and which would accelerate the long-standing trend to low or very low fertility rates.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, an increase in social support and interactions at an educational institute decreases burnout and enhances well-being [39]. Importantly, recently conducted studies have found that during the Covid-19 pandemic, relationship quality decreased, and that this result was driven mostly by the emotional stressor [44]. According to Pieh et al [40], compared to no relationship, a good relationship quality was a protective factor, whereas a poor relationship quality was a risk factor for mental health during the Covid-19 pandemic lockdown.…”
Section: Research Question 4 Does Quality Of Social Relationships Dur...mentioning
confidence: 99%
“…These containment measures had led to major disruptions in social and family life (Mayer, 2022; OECD, 2021a, 2021b). They also resulted in increased stress and relationship struggles (Bellani & Vignoli, 2022)—factors that are negatively associated with an intention to become pregnant (Manning et al, 2022; Tasneem et al, 2023). At the same time, economic support cushioned financial pressure and economic uncertainty.…”
Section: Introductionmentioning
confidence: 99%